2006
DOI: 10.1097/01.hjh.0000234118.25401.1c
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of blood pressure and cholesterol in stage 1 hypertension: role of autonomic nervous system activity

Abstract: These data indicate that a condition characterized by sympathetic predominance may favour the development of sustained hypertension and hypercholesterolemia early in life, and lead to increased susceptibility to vascular complications. They further indicate that the increased white-coat effect is not an innocent phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 33 publications
6
29
0
1
Order By: Relevance
“…Although the predictive value for HDL cholesterol is not entirely in line with our previous results-we only found a cross-sectional relationship between HDL cholesterol and HR-it does match with other cross-sectional results (17,19,62). Our BP and HDL cholesterol findings perfectly match those of Palatini et al (6). In a study on hypertension and lipid abnormalities, they reported that subjects with sympathetic predominance (high sympathetic activity relative to low parasympathetic activity) showed increased BP (systolic as well as diastolic) and total cholesterol levels at 6-year follow-up compared to the subjects without autonomic dysregulations.…”
Section: Discussionsupporting
confidence: 82%
“…Although the predictive value for HDL cholesterol is not entirely in line with our previous results-we only found a cross-sectional relationship between HDL cholesterol and HR-it does match with other cross-sectional results (17,19,62). Our BP and HDL cholesterol findings perfectly match those of Palatini et al (6). In a study on hypertension and lipid abnormalities, they reported that subjects with sympathetic predominance (high sympathetic activity relative to low parasympathetic activity) showed increased BP (systolic as well as diastolic) and total cholesterol levels at 6-year follow-up compared to the subjects without autonomic dysregulations.…”
Section: Discussionsupporting
confidence: 82%
“…Sympathetic predominance is both a risk factor for developing sustained hypertension [2] and for developing cardiovascular disease (CVD) in those with sustained hypertension [3,4]. Markers of sympathetic activity such as norepinephrine (NE) levels are generally higher in hypertensives than normotensives, both at baseline and when confronted with a psychosocial stressor [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…There are data that strongly indicate that hypertension in the young occurs in those with sympathetic predominance [75]. Younger hypertensives do indeed have an approximate 2-fold increase in sympathetic activity compared to normotensive controls [76], closely linked to obesity and the biochemical changes associated with the metabolic syndrome [57,77].…”
Section: B)mentioning
confidence: 97%